Energy, Exergy, and Externalities Cost Rate Analysis of 300 MW Coal-Fired Power Plant: A Case Study (Majalah Ilmiah Pengkajian Industri, 2022)
Three types of analysis conducted at one of Thailand's coal-fired power plants were reported in this paper. The analyses consisting of energy, exergy, and externalities cost rate analysis are aimed to analyse the largest energy loss and exergy destruction that occurs in the system, to assess the contribution of Energy externalities cost rate based on fuel price, and to determine potential cost saving. Energy loss at the condenser was the highest among major units of the Thai power plants, which contributed around 49.11% at full load condition and was followed by a boiler, turbine, etc. Furthermore, the boiler was identified as the highest exergy destruction producer, with around 57.73% of total exergy input into the system, followed by turbines, heaters, etc. Moreover, the energy and exergy efficiency of Thai's power plant was calculated to be around 35.60% and 31.76%, respectively. The highest externalities cost rate due to energy loss occurred in the condenser was about 0.56 $/s, whereas the highest externalities cost rate due to exergy destruction identified in the boiler was about 0.67 $/s. By improving boiler and turbine components, Thai's PP has a potential cost saving of around 21.2 million $/year, reducing 88.44% of the externalities cost of exergy destruction.  Keywords:  Energy loss, Exergy destruction, Externalities cost rate, Potential saving cost.